Characterization of table tennis racket sandwich rubbers - Major, Z.; Lang, R. W. (Journal of Sports Sciences, 2006)
In table tennis recently complex racket designs are used consisting of a wooden or glass or carbon fiber reinforced racket frame with multi-layer rubber/foam covers with special top surface properties. Various rubber compounds and glues (adhesives) are applied in the build up of the multi-layer rubber foam cover to impart greater spin or speed (up to 160 km/h) onto the celluloid ball. In terms of material characteristics, important aspects of a successful table tennis racket design are related to the elasticity and damping of the entire sandwich system and the specific surface properties that generate the spin of the celluloid ball upon the impact contact with the rubber surface.